Peran Guru Kelas dan Guru Pendamping Khusus Dalam Proses Pembelajaran Bagi Anak Berkebutuhan Khusus di Kelas 6A Sekolah Dasar Negeri - Catur Putri Aisyah; Arnadi; Novi Cahya Dewi (putrapublisher.org, 2023)
The aim of this research is to describe and find out about: the role of class teachers and special assistant teachers in planning learning for children with special needs in class 6A at SD Negeri 4 Nagur, the role of class teachers and special assistant teachers in implementing learning for children with special needs in class 6A SD Negeri 4 Nagur, the role of class teachers and special assistant teachers in evaluating learning for children with special needs in class 6A SD Negeri 4 Nagur. This research uses a qualitative approach and the type of research used is descriptive. The data collection techniques used were interviews, observation and documentation. Then the data analysis techniques used in this research are data reduction, data display/data presentation, and drawing conclusions. Meanwhile, researchers' data validity checking techniques use triangulation and member checking. The results of this research show that: the learning implementation plan or RPP prepared by the class teacher is the same as the RPP for regular students. The accompanying teacher also acts spontaneously in simplifying the learning material delivered by the class teacher which is adapted to the abilities of students with special needs, implementing learning for children with special needs, the accompanying teacher guides and accompanies children with special needs individually. The accompanying teacher delivers the learning material delivered by the class teacher with learning strategies and learning methods adapted to the child's abilities with simplified material, 3) Evaluation questions and indicators of achievement of understanding are adjusted to the child's abilities. The evaluation questions are made simpler both in terms of material, level of difficulty, simplification of words and sentences